Using Audio-Lingual-Method to Overcome Student’s Listening Problem In Senior High School Kartika Pematangsiantar - Rutlina Elfeliani Sihombing; Yerani Apriyanti Silalahi; Trimeli Tamara Sianturi; Kristen Panjaitan; Selviana Napitupulu (Ilmu Inovasi Nusantara, 2022)
Listening is one of the basic skills in learning English. Teaching listening to students is significant, as listening to itself is crucially important in life. Those who do not know how to listen cannot listen to their family friends and understand what is said. Listening has been taught since junior high school through audio, video, songs, games. However, there are still many students who have difficulty listening. Then after we made observations in Senior High School Kartika Pematangsiantar, we researchers found that students did not catch every word they heard. So, as a solution to these problems, teachers can use exciting teaching methods to present teaching materials that also help them create fun classes, namely the Audio-lingual teaching method. The audio-lingual method is one method that aims to emphasize word repetition, which allows students to more easily use the target language so that it is easy to understand